AS CLÁUSULAS DE VALOR NOS CRIMES DE FURTO QUALIFICADO E A RESERVA DA LEI EM MATÉRIA PENAL: UMA REVISITAÇÃO E UM APROFUNDAMENTO: José de Faria Costa (De Legibus - Law Journal, 2021)
The text critically analyzes the evolution, in the portuguese legalsystem, of the clauses of value used for the qualiﬁcation of the thef crime, reachingthe conclusion that the model currently adopted implies some diﬃculties towardsthe principle of legal reserve in criminal matters.